2024
DOI: 10.3389/fimmu.2024.1353889
|View full text |Cite
|
Sign up to set email alerts
|

Real-world impact of the introduction of chemo-immunotherapy in extended small cell lung cancer: a multicentric analysis

Laura Bonanno,
Lorenzo Calvetti,
Alessandro Dal Maso
et al.

Abstract: BackgroundRecent clinical trials demonstrated longer survival in extended small cell lung cancer (SCLC) patients treated with immunotherapy in addition to chemotherapy. However, the magnitude of benefit is modest and the impact in real-world setting has to be fully established.MethodsWe collected clinical data and radiological imaging of patients affected by extended or relapsing SCLC and consecutively treated according to clinical practice between 2016 and 2023. As primary end-point, we compared pre-defined o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Survival outcomes are comparable to previous real-world data and negatively influenced by the inclusion of patients with poor performance status, active brain metastasis, comorbidity and with a high disease burden, generally excluded from large randomized clinical trial. 27–30 …”
Section: Discussionmentioning
confidence: 99%
“…Survival outcomes are comparable to previous real-world data and negatively influenced by the inclusion of patients with poor performance status, active brain metastasis, comorbidity and with a high disease burden, generally excluded from large randomized clinical trial. 27–30 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the real-world study by Zheng et al, included in this Research Topic, confirmed the data coming from phase III trials in terms of survival benefit but also pointed out the presence of a subgroup of long-term surviving patients benefiting from first-line chemo-immunotherapy and less likely to need further lines of treatment. Such a result is impressive for a disease that is so challenging to treat that it was officially defined as a "recalcitrant cancer" (11). Unluckily, there is still an unmet need regarding predictive tools able to identify patients who would benefit longer from first-line chemo-immunotherapy (12).…”
mentioning
confidence: 99%